2016
DOI: 10.1371/journal.pone.0159531
|View full text |Cite
|
Sign up to set email alerts
|

XRP44X, an Inhibitor of Ras/Erk Activation of the Transcription Factor Elk3, Inhibits Tumour Growth and Metastasis in Mice

Abstract: Transcription factors have an important role in cancer but are difficult targets for the development of tumour therapies. These factors include the Ets family, and in this study Elk3 that is activated by Ras oncogene /Erk signalling, and is involved in angiogenesis, malignant progression and epithelial-mesenchymal type processes. We previously described the identification and in-vitro characterisation of an inhibitor of Ras / Erk activation of Elk3 that also affects microtubules, XRP44X. We now report an initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 59 publications
(71 reference statements)
1
23
0
Order By: Relevance
“…Finally, we tested an inhibitor of ELK3 signaling, XRP44X, in N2a cells Semenchenko et al, 2016). Two hours of inhibition with higher doses of XRP44X showed more potent increases in progranulin levels (Fig.…”
Section: Small-molecule Inhibitors Enhance Progranulin Levels In N2a mentioning
confidence: 99%
“…Finally, we tested an inhibitor of ELK3 signaling, XRP44X, in N2a cells Semenchenko et al, 2016). Two hours of inhibition with higher doses of XRP44X showed more potent increases in progranulin levels (Fig.…”
Section: Small-molecule Inhibitors Enhance Progranulin Levels In N2a mentioning
confidence: 99%
“…ELK3 (also called Net, SAP-2, or ERP) is an ETS domaincontaining transcription factor that forms a ternary complex transcription factor (TCF) together with ELK-1 and serum response factor accessory protein-1 (SAP-1) and binds to a specific DNA sequence through a purine-rich GGA core sequence to regulate the expression of many genes including proto-oncogenes [6,7]. Under basal conditions, ELK3 is a transcriptional repressor, which converts to a transcriptional activator in response to ratsarcoma viral oncogene homolog/ extracellular regulated protein kinases (RAS/ERK) signaling and p38 mitogen-activated protein kinase (MAPK) pathway [8][9][10], and is involved in cell migration, angiogenesis, and malignant progression [11][12][13][14]. Several studies have showed that ELK3 is overexpressed in some cancer cells and correlates with cell migration and invasion [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Under basal conditions, ELK3 is a transcriptional repressor, which converts to a transcriptional activator in response to ratsarcoma viral oncogene homolog/ extracellular regulated protein kinases (RAS/ERK) signaling and p38 mitogen-activated protein kinase (MAPK) pathway [8][9][10], and is involved in cell migration, angiogenesis, and malignant progression [11][12][13][14]. Several studies have showed that ELK3 is overexpressed in some cancer cells and correlates with cell migration and invasion [13][14][15]. Hypoxiainducible factor-1α (HIF-1α) can regulate the genes related to cell proliferation, apoptosis, angiogenesis, and metastasis, playing an important role in cancer progression [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The potential value of ELK3 as a target of anticancer drug development is supported by the fact that TNBCs with reduced ELK3 activity completely lost their metastatic characteristics (12). It was shown that small molecule based inhibition of Ras/ERK-mediated ELK3 activity results in the inhibition of prostate cancer progression and metastasis in mice (20). It would be interesting to investigate whether simultaneous inhibition of the TGFβ pathway and ELK3 activity produces clinically effective therapeutic outcomes.…”
Section: Discussionmentioning
confidence: 99%